Dynamics of Deflationary Pressure in China: Causes, Consequences, and Policy Implications: Hendri Khuan Universal Institute of Professional Management Email: hendri.khuan@gmail.com - Hendri Khuan (Universal Institute of Professional Management, 2023)
The study investigates the dynamics of deflationary pressure in China, aiming to discern its causes, consequences, and policy implications through a comprehensive bibliometric analysis. The analysis employs co-citation networks, high-citation articles, and keyword frequency to map the research landscape surrounding deflation within China's economic context. The results reveal distinct clusters of research themes, influential articles, and frequently occurring keywords. Notably, these insights showcase the intricate interactions between economic growth, monetary policy, exchange rates, competitiveness, and globalization in deflation. The study contributes to an enriched understanding of the multifaceted challenges and opportunities associated with deflation in China, offering insights to guide policy decisions and future research.